2009
DOI: 10.4049/jimmunol.0803007
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Osteoclast Differentiation Induced by IL-1

Abstract: IL-1 is a potent cytokine that can induce bone erosion in inflammatory sites such as rheumatoid joint regions via activation of osteoclasts. Not only is IL-1 capable of activating osteoclasts, but it is also a key cytokine involved in the differentiation, multinucleation, and survival of osteoclasts. Herein, we show that IL-1 has the potential to drive osteoclast differentiation via a receptor activator of NF-κB ligand (RANKL)/RANK-independent mechanism. Although IL-1 has a synergistic effect on RANKL-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
175
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 233 publications
(186 citation statements)
references
References 47 publications
6
175
1
4
Order By: Relevance
“…Recently, it has been found that NFATc1 functions in the osteoclast fusion process via up-regulation of the dendritic cell-specific transmembrane protein (DC-STAMP) and the d2 isoform of vacuolar ATPase V0 domain (Atp6v0d2) through co-activation with MEF2 and MITF, which would be followed [58,59]. Moreover, interleukin-1 (IL-1) activates osteoclast-specific genes including TRAP and OSCAR, in part, via the MITF pathway [61]. Mi mutant osteoclasts are primarily mononuclear and express decreased levels of TRAP [41,62].…”
Section: Molecular Control Of Osteoclast Differentiationmentioning
confidence: 99%
“…Recently, it has been found that NFATc1 functions in the osteoclast fusion process via up-regulation of the dendritic cell-specific transmembrane protein (DC-STAMP) and the d2 isoform of vacuolar ATPase V0 domain (Atp6v0d2) through co-activation with MEF2 and MITF, which would be followed [58,59]. Moreover, interleukin-1 (IL-1) activates osteoclast-specific genes including TRAP and OSCAR, in part, via the MITF pathway [61]. Mi mutant osteoclasts are primarily mononuclear and express decreased levels of TRAP [41,62].…”
Section: Molecular Control Of Osteoclast Differentiationmentioning
confidence: 99%
“…10,19,20 This is particularly relevant in relation to post-menopausal bone loss, where estrogen depletion results in increased production and release of IL-1, and subsequently osteoclast formation and bone resorption. 21 It has been demonstrated that P2X7 is involved in mechanically induced signalling between osteoblasts and osteoclasts, 14 as well as with osteoclast survival. 12,17,22 Furthermore, it has been shown to couple to NF-kB in osteoclasts.…”
Section: Introductionmentioning
confidence: 99%
“…A previous report demonstrated that overexpression of IL-1 in bone marrow macrophages (BMMs) resulted in the activation of NF-kB, JNK, p38, and the extracellular signal-regulated kinases (ERK) pathway, which is a hallmark of osteoclast differentiation, and also enhanced microphthalmia-associated transcription factor activity, thereby inducing the expression of osteoclast marker genes such as osteoclast-associated receptor (OSCAR) and tartrate-resistant acid phosphatase (TRAP). (10) Therefore, the actions of these proinflammatory cytokines affect the balance between bone mineralization and resorption regulated by the opposing actions of osteoblasts and osteoclasts.…”
Section: Introductionmentioning
confidence: 99%